P054 Secreted inflammatory protein profiles following treatment of ex-vivo human inflammatory bowel disease explants with licenced biologic therapies. (30th January 2023) - Corcoran, R; O'Connell, F; O'Sullivan, J; Kevans, D
Abstract: Background: Patient-derived inflammatory bowel disease (IBD) ex-plants have potential for biomarker and therapy discovery. Infliximab (IFX), ustekinumab (USTK) and vedolizumab (VDZ) are biologic therapies licenced for the induction and maintenance of remission in ulcerative colitis (UC) and Crohn's disease (CD). All are efficacious in IBD despite differing mechanisms of action. Treatment of IBD explants ex-vivo with licensed biologic therapies may result in further insights into their mechanism of action. We aimed to evaluate the effect of IFX, USTK and VDZ on inflammatory protein secretion profiles in ex-vivo human IBD ex-plants. Methods: Patients with IBD, undergoing endoscopy, were prospectively recruited. Biopsies were collected from the sigmoid and IBD ex-plants generated as per previously described methods. IBD explants were then co-cultured for 24 hours with an IgG control vehicle, IFX, USTK and VDZ. After 24 hours, tissue conditioned media (TCM) from IBD explants was collected. TCM secreted inflammatory protein profiles were quantified using 54 V-plex ELISA (Meso Scale Diagnostics, USA). Secreted inflammatory protein profiles were compared between IgG vehicle (control) and USTK, IFX, VDZ treated ex-plants. All continuous variables are presented as median [interquartile range (IQR)]. P values < 0.05 were considered significant in analyses. Results: 37 patients with IBD were included (51% CD, 49% UC); age (median, [IQR]) 41[33-53] years, 49% male; disease duration (median, [IQR]) 9 [5-14] years; 51% of patients were anti-TNF naïve. TNF-a secretion was significantly lower in IBD explants treated with IFX compared with IgG control, p=0.006. IL-23 secretion was significantly lower in IBD explants treated with USTK compared with IgG control, p=0.043. Biologic therapy ex-vivo resulted in significant differences in angiogenesis and vascular injury panel biomarkers compared to control; CRP, VEGF-A and SAA. Pro-inflammatory cytokines and chemokines were also significantly decreased with ex-vivo biologic therapy compared to control; IL-2, IL-10, IL-6, MCP-1, IL-1a, TNF-a and MDC. Three Th17 panel proteins were significantly decreased with ex-vivo biologic therapy compared to control; IL-22, IL-17A, IL17A Gen B. Conclusion: The statistically significant decrease in both TNF-a and IL-23 secretion with ex vivo IFX and USTK treatment respectively demonstrates that the IBD explant model recapitulates expected IBD disease biology and therapy responses. These data demonstrate that treatment with licenced biologic therapies ex-vivo reduces multiple pro-inflammatory cytokines, chemokines and secreted proteins in IBD explants. Further study is required to completely understand the effects of licenced biologic therapies on the IBD tissue microenvironment.